2018
DOI: 10.15761/srj.1000147
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case: Adult giant pyonephrosis

Abstract: Pyonephrosis is a disease, causing suppurative destruction of the renal parenchyma. Fever, chills, and flank pain are most commonly seen. Clinical presentation can include a huge spectrum from asymptomatic bacteriuria (15%) to urinary sepsis, septic shock and death. Palpable abdominal mass, associated with the hydronephrotic kidney can be detected during physical examination. Urinary system infections, obstruction and anatomic variations (such as pelvic kidney, horseshoe kidney) play a role in etiology. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The surgical procedure of choice is nephrectomy if the contralateral kidney is healthy; if a nephrostomy is inserted on an emergency basis, nephrectomy can be performed once the patient's overall health has improved, often after two weeks. 2,3 Some cases of giant pyonephrosis have been reported previously from different countries; however, this is the first case reported in our country, if not from Africa, and a case of giant pyonephrosis measuring 13 cm × 24 cm × 34 cm (7 litres of pus) caused by an obstructed stone. They performed a simple nephrectomy through a large midline incision, and a similar case of giant pyonephrosis from the same country was reported four years later and treated with simple nephrectomy.…”
Section: Dovepressmentioning
confidence: 73%
See 3 more Smart Citations
“…The surgical procedure of choice is nephrectomy if the contralateral kidney is healthy; if a nephrostomy is inserted on an emergency basis, nephrectomy can be performed once the patient's overall health has improved, often after two weeks. 2,3 Some cases of giant pyonephrosis have been reported previously from different countries; however, this is the first case reported in our country, if not from Africa, and a case of giant pyonephrosis measuring 13 cm × 24 cm × 34 cm (7 litres of pus) caused by an obstructed stone. They performed a simple nephrectomy through a large midline incision, and a similar case of giant pyonephrosis from the same country was reported four years later and treated with simple nephrectomy.…”
Section: Dovepressmentioning
confidence: 73%
“…They performed a simple nephrectomy through a large midline incision, and a similar case of giant pyonephrosis from the same country was reported four years later and treated with simple nephrectomy. 3 , 8 An open nephrectomy was used to treat a case of giant pyonephrosis measuring 23 cm × 30 cm × 27.9 cm which was caused by urolithiasis and diabetes, as reported by Hasigov et al 9 Rupesh Gupta et al had reported a case of giant pyonephrosis of size 30 cm × 26 cm × 20 cm (12 liters of pus) due to Ureteropelvic Junction Obstruction and they have done nephrectomy through subcostal incision. 9 Niang et al recently reported a case of giant pyonephrosis containing 10 liters of pus and spontaneously ruptured in the adjacent muscles and the treatment was an aspiration followed by a nephrectomy by laparotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Selviet et al, the most common intraoperative incidents in these patients are injuries to the colon (most usually on the left), duodenum, inferior vena cava, laceration of the inferior pole of the spleen, and unintentional opening of the pleural or peritoneal cavity. Postoperative colic, ileus, severe thrombophlebitis, and surgical wound suppuration are common postoperative sequelae [ 10 ].…”
Section: Discussionmentioning
confidence: 99%